Bioelectrical impedance devices in clinical practice: a narrative review - Fabio Benedetti Rodrigues; Pedro Bertemes-Filho (Academia Medicine)
The increase in the world population renders constant the search for innovative health technologies. Bioelectrical impedance is in the spotlight because of its wide range of uses and its inexpensiveness compared to other non-invasive technologies. Bioelectrical impedance can monitor the body composition by estimating the nutrition status, obesity levels, and the hydration status. Beyond this, it can help in mechanical ventilation and measure glucose in a non-invasive way. So why has this technology been less used in clinical practice? One of the answers concerns how little information physicians have access to in the literature on bioelectrical impedance devices. This is a multifactorial problem that ranges from the specific database used to the way in which the articles are written. This narrative review aims to bring bioelectric impedance knowledge closer to health care workers. Therefore, we have simplified the technical information and prioritized the use indications, making the information more accessible to health care professionals.